A Review of Equine Laparoscopy. (24th October 2012) - Hendrickson, Dean A.
Abstract : Minimally invasive surgery in the human was first identified in mid 900's. The procedure as is more commonly practiced now was first reported in 1912. There have been many advances and new techniques developed in the past 100 years. Equine laparoscopy, was first reported in the 1970's, and similarly has undergone much transformation in the last 40 years. It is now considered the standard of care in many surgical techniques such as cryptorchidectomy, ovariectomy, nephrosplenic space ablation, standing abdominal exploratory, and many other reproductive surgeries. This manuscript describes the history of minimally invasive surgery, and highlights many of the techniques that are currently performed in equine surgery. Special attention is given to instrumentation, ligating techniques, and the surgical principles of equine minimally invasive surgery.